EFEKTIVITAS PENGGUNAAN METODE THINK PAIR SHARE DALAM PEMBELAJARAN EKONOMI POKOK BAHASAN PEMBENTUKAN HARGA PASAR DI SMP - Widodo, Joko (Fakultas Ekonomi, Universitas Negeri Semarang, 2007)
The result of teaching-learning by using Think Pair Share method can improve the studentsÃ¢â‚¬â„¢ activities. It can be seen from the steps to apply the Think Pair Share method that focused on student-centre. Think pair share learning has a simple structure, as a basic of the development Ã¢â‚¬Ëœcooperative classÃ¢â‚¬â„¢ which can help the learning process actively for students, thus it can improve the studentsÃ¢â‚¬â„¢ study result. Students actively can show their ability to discuss and share and express the answer of questions in front of the class. Teachers in teaching- learning process by using think pair share method acted as mediator, facilitator and motivator. It is different with conventional teaching-learning process which focused on teacher-center. Students were passive in teaching-learning process. Students tended to be bored if the teacher was lack to give motivation for students to pay attention to the teacher. Thus, the using of think pair share would be more effective if we see on how the students interaction in learning process. Teacher can vary think pair share with conventional method or other method to improve the studentsÃ¢â‚¬â„¢ activities in learning process, therefore the studentsÃ¢â‚¬â„¢ result study will be increased. Ã‚Â Keywords: Think-pair-share, the increase of result study.